(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study investigated the Influence of Girl Child Education on Women Empowerment in Jalingo Educational Zone of Taraba State, Nigeria. Research objectives, questions and hypotheses were formulated. A descriptive survey research design was employed with a population of 5,323 participants comprising 4,450 SSS II female students and 873 female teachers from public senior secondary schools. A sample size of 372 respondents (23.3% of the population) was selected. Data collection utilized the "Influence of Girl-child Education and Women Empowerment Questionnaire (GEPWEQ)" with a reliability coefficient of 0.94 using Cronbach’s Alpha method. The instrument featured a 4-point likert scale with 45 items across two sections. Chi-square statistical analysis was employed to test the research hypotheses at 0.05 significance level. While data was analysed based on the questions and hypotheses raised using SPSS Version 23. The study revealed significant positive influences of girl child education on women empowerment. Both null hypotheses were rejected, establishing that girl child education significantly impacts both income and occupational empowerment dimensions. The study recommends implementing public enlightenment programs on gender equality, establishing motivational counselling systems for female students, organizing professional development workshops for educators, and developing admission criteria that favour girls’ education.